تاريخ الجزائر الثقافي من خلال موسوعة ابو قاسم سعد الله المجلد الأول، الثاني، الرابع - سامية دراجي; عرباوي عبير (My University, 2023)
Abstract : This studyattempts to shed light on the cultural situation of Algeria during the Ottoman erathrough the encyclopedia of Abu al-Qasim Saad Allah. It initiallyincluded a biographicalstudy about the personality of the historian and professor Abu al-Qasim Saad Allah, hisscientificachievements and hiseducationalactivity, in addition to hismethodology in writinghistory. Wealsostudiedmany institutions. Wealsolearned about the mostprominent sciences thatwereknown in Algeria during the Ottoman era, as well as some of the flags and personalitiesthatwerefamous in Algeria during the sameperiod. In the last chapter, wetried to identify Abu al-Qasim Saadallah's position on the cultural situation in Algeria during the Ottoman era, and wealsostudied the opinions of somehistorians and professors about Saadallah'sviews and perceptions. ------------------------------------------------------------------------------- الملخص تحاول هذه الدراسة تسليط الضوء على الوضع الثقافي للجزائر خلال العهد العثماني من خلال موسوعة أبو القاسم سعد الله ، وقد تضمنت في البداية دراسة بيوغرافية حول شخصية المؤرخ والأستاذ أبو القاسم سعد الله ومنجزاته العلمية ونشاطه التعليمي بالإضافة إلى منهجه في كتابة التاريخ، كما درسنا العديد من المؤسسات الثقافية التي تطرقت لها الموسوعة، كما تعرفنا على أبرز العلوم التي كانت معروفة في الجزائر خلال العهد العثماني، وأيضا بعض الأعلام والشخصيات التي اشتهرت في الجزائر خلال نفس الفترة. وفي الفصل الأخير حاولنا التعرف على موقف أبو القاسم سعد الله من الوضع الثقافي للجزائر خلال العهد العثماني، ودرسنا أيضا آراء بعض المؤرخين والأساتذة حول آراء سعد الله وتصوراته.